RANCANG BANGUN APLIKASI PEMBUATAN KARTU TANDA PENDUDUK NON-PERMANEN KELURAHAN PAGESANGAN BARAT BERBASIS DESKTOP: Desktop-Based Application to Make an ID Card for Non-Permanent Resident in Pagesangan Barat Sub District - Chandra Adiguna; I Gede Pasek Suta Wijaya; Lalu Sweta Arif (Jurnal Begawe Teknologi Informasi (JBegaTI), 2020)
As a number of increasing a non-permanent resident in Mataram especially in Pagesangan Barat, this will also increase the number of problem like theft and robbery because of their ID are not recorded on the local government and also when a non-permanent resident got an accident when they live in Pagesangan Barat the local government can contact their parents to tell them of that accident that happened to their family in Pagesangan Barat. Therefore, based on that problem, we develop a desktop-based application to minimize that problem occur in Pagesangan Barat. This application was designed to provide some information about non-permanent resident, boarding house and this application also can make an ID card for non-permanent resident that already registered on the system. Meanwhile, for non-permanent resident that has not non-permanent resident ID card, they will not to serve by local government. The system testing technique which was used in this researd were blackbox testing. The result of blackbox testing on the application showed that all features can be run as planned.